RANCANG BANGUN SISTEM PENGGAJIAN BERBASIS WEB DENGAN MODEL SEKUENSIAL LINIER - Komang Agustia Trimiharta; Eddy Muntina Dharma; Anak Agung Ayu Redi Pudyanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
A banking company has a goal to improve the economy and people's welfare. In addition, banking companies such as PT. BPR Suadana must also improve employee performance and welfare. One way is to increase performance in the form of salary. Payroll system at PT. BPR Suadana currently looks still manual. Where in the salary input is still recorded manually. This makes time inefficient and increases the risk of errors in the payroll process. This study aims to build an information system used in the payroll system at PT. BPR Suadana. The method used in the construction of this payroll system is the Linear Sequential Model SDLC method. The results of this research are in the form of a web-based payroll system that can be accessed and used by related divisions, namely HRD, Funds Section, and also the Director. the results of the TAM test that has been carried out by the author, it can be seen that the percentage results of 88% of users or respondents stated strongly agree and 8% agreed, that the payroll system at PT. BPR Suadana that has been made by the author is easy to use and very useful in overcoming payroll problems at PT. BPR Suadana.